POLICY FLIGHT SIMULATORS: ACCELERATING DECISIONS TO ADOPT EVIDENCE-BASED HEALTH INTERVENTIONS. (11th November 2018) - Yu, Z; Rouse, W; Naylor, M D; Pennock, M J; Hirschman, K B; Pauly, M V; Pepe, K
Abstract: The purpose of this study was to explore the economic impact of the use of the Transitional Care Model (TCM) using publicly available CMS data on 3000+ hospitals in the U.S. and TCM data. Four simulations explored the: 1) magnitude of readmission penalty; 2) application to specific diagnosis related groups; 3) level of cost sharing between payer and provider; and 4) capitated versus fee-for-service payments. The simulator projected hospital-specific impacts. Under current conditions, only 15 of 3000+ Medicare certified hospitals would see a financial benefit from TCM for all patients. Current CMS penalties have little effect on the economic attractiveness of TCM. Payers cost sharing increases attractiveness; 100% coverage makes TCM attractive to 2000 hospitals. Capitated payment makes TCM attractive to approximately 1500 hospitals. Current CMS penalties have little effect on the economic attractiveness of TCM. Additional strategies to facilitate TCM adoption and policy and research implications will be discussed.